Kajian Atmosfer Spasial Masjid Nur Andakara Berdasarkan Kinerja Bangunan - Faiz Suprahman (Universitas Muhammadiyah Palembang, 2026)
The spatial atmosphere in the architectural realm is defined by Gernot Böhme as the quality perceived by the user of the space through sensory experience. This sensory experience serves as an indicator of the success of architectural design. However, the theory provided still needs to be studied through more empirical architectural planning cases. Through the evaluation of the performance of the Nur Andakara Mosque building, this study focuses on understanding the variables that form the atmosphere and its generators in the three atmospheric characters proposed by Böhme: impression of motion, synaesthesia, and social character. The relationship between the elements that form the space and the atmosphere that appears is studied to provide a complete picture of the performance of a building built with a certain design intensity. The results of this study identify the elements of the building planned into the three characters, along with their impact on the quality of the design, in terms of the impression of motion formed by the accessibility elements in the building. The use of materials and thermal control operations becomes synaesthetic characters. Processing the shape of both the exterior and interior into social characters. The results of this study contribute to the design strategy in similar design cases, enabling them to achieve the quality of the spatial atmosphere.